Trust in international police and justice cooperation - Hufnagel, Saskia; McCartney, Carole; McCartney, Carole (Oñati international series in law and society, 2017)
Establishing trust despite the risk? an analysis of the need for trust in police cooperation / Ludo Block (Grant Thornton, NL) -- Police cooperation in Europe, China, and Australia : does trust depend on the political system? / Saskia Hufnagel (Queen Mary University of London) -- International policing missions : establishing trustworthy policing in low-trust environments / Andrew Goldsmith (Flinders University, Australia) and Vandra Harris (RMIT, Australia) -- Trusted travellers : managing mobility in challenging times / Monica den Boer (Vu Amsterdam) and Hans Leijtens (Ministry of Finance, NL) -- Brand interpol / James Sheptycki (York University, Canada) -- The evolving role of Europol in the fight against serious crime : current challenges and future prospects / Celine Cocq and Francesca Galli (Free University of Brussels) -- Building trust and more : the importance of police cooperation networks in the European Union / Toine Spapens (Tilburg University) -- Trust and the international exchange of forensic information / Carole McCartney (Northumbria University) -- Law enforcement cooperation between New Zealand and the United States : serving the Internet?pirate? Kim Dotcom up on a silver platter?? / Neil Boister (Waikato University, Newzealand) -- Transnational policing and its contexts : flexibility and (dis)trust / Chantal Perras (University of Montreal) -- Intelligence-led use of international forensic exchange channels / Denise Sulca (University of Lausanne)